2003
DOI: 10.1093/mutage/geg022
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic biomonitoring in petrol station attendants: micronucleus test in exfoliated buccal cells

Abstract: To study the effects of occupational exposure to petroleum derivates such as benzene, exfoliated buccal cells from 50 petrol station attendants and 50 age- and sex-matched control subjects were examined for micronucleus (MN) frequency. Frequencies of nuclear abnormalities (NA) other than micronuclei, such as binucleates, karyorrhexis and karyolysis, were also evaluated. Benzene exposure was ascertained by measuring urinary phenol levels. The mean urinary phenol level of station workers was found to be signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
80
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 29 publications
17
80
2
2
Order By: Relevance
“…Regarding ONA, and fully in line with our observations, Martins et al [22] found that tobacco smoking did not significantly interfere with the cytotoxicity induced by petroleum derivates in buccal mucosa cells or in the lateral border epithelium of the tongue in petrol-station attendants. On the other hand, Ç elik et al [32] report that tobacco use increased significantly the risk of having a high frequency of bi-nucleated cells, but the individuals in their study were heavy smokers (20-25 cigarettes/day), contrary to those in the present study (7.5-16 cigarettes/day).…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Regarding ONA, and fully in line with our observations, Martins et al [22] found that tobacco smoking did not significantly interfere with the cytotoxicity induced by petroleum derivates in buccal mucosa cells or in the lateral border epithelium of the tongue in petrol-station attendants. On the other hand, Ç elik et al [32] report that tobacco use increased significantly the risk of having a high frequency of bi-nucleated cells, but the individuals in their study were heavy smokers (20-25 cigarettes/day), contrary to those in the present study (7.5-16 cigarettes/day).…”
Section: Discussioncontrasting
confidence: 92%
“…The frequency of MNC in the administrative workers was lower than 1 per 1000 cells, which is within the normal range for the human oral epithelium (0.5-2.5 MNC/1000) as reported by Holland et al [11] and Ceppi et al [26]. The higher frequency of MNC observed among the group exposed to VOCs is also in line with other studies, especially those focusing on exposure to diesel fuel and vehicle exhaust [21,22,[31][32][33]. On the other hand, exposure to VOCs was not related to the frequency of ONA (karyorrhexis, karyolysis, and pyknosis).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…39 A study reported that it is a nuclear abnormality seen in dysplastic cells and is seen to be increased in smokers. 46 In the present study significant increase in binucleation frequency was observed in smokers group.…”
Section: Discussionsupporting
confidence: 61%